Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Solve: 3(3y+7)+13=10(−2y−2)−4.

Sagot :

Answer:

-2

Step-by-step explanation:

3(3y+7)+13=10(-2y-2)-4

9y+21+13=-20y-20-4

9y+20y= -21-13-20-4

29y= -58

Y= -58/29

Y= -2

Answer:

y = -2

Step-by-step explanation:

3(3y+7) + 13 = 10(−2y − 2) − 4,

9y + 21 + 13 = -20y - 20 - 4,

9y + 34 = -20y - 24,

29y = -58,

y = -2